A rare association of puerperal ovarian venous thrombosis with pseudomembranous colitis - Kamat, Devika J.; Kavlekar, Namrata P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Ovarian venous thrombosis is a rare but serious complication associated with early puerperium. The risk of this complication increases with associated puerperal infection or inflammatory condition. The present case report is of a 36-year-old lady who presented after emergency caesarean with puerperal fever and abdominal pain along with diarrhoea post antibiotic cover. Patient presented with moderate ascites and uterine subinvolution on examination. Contrast enhanced computed tomography (CECT) showed evidence of bowel wall edema due of colitis along with ovarian vein thrombosis. Patients had persistent symptoms despite receiving an empirical course of injectable cephalosporins. Stool culture confirmed growth of Clostridium difficile. Patient developed a rare infection after a course of antibiotic i.e. pseudomembranous colitis caused by Clostridium difficile. Patient then received a course of injectable vancomycin after which colitis subsided. This case increases our vigilance on management of puerperal fever which could get complicated with life-threatening events like deep vein thrombosis.